A Correlation Study Between Physical Literacy And Sport Values In Junior High School In Bandung City - Rita Dela Puspitasari; Oom Rohmah; Amung Ma’mun; Syarifatunnisa; Anira (Universitas Negeri Semarang, 2024)
Problems with physical literacy in schools cover a wide range of aspects that can affect students' health and well-being. Common problems include lack of time for physical education, inadequate facilities, low prioritization of physical activity, and lack of awareness about the health benefits, among others. In Indonesia, physical literacy is a new idea that is developing in Indonesia. The purpose of this study was to analyze how physical literacy relates to sport values. This study used cross sectional survey research. This study involved 111 junior high school students in Bandung City, (male = 48 people; female = 63 people) with an age range of 12-15 years. The results showed that there was a relationship between physical literacy and sport values (r = 0.469; Sig < 0.001). The resulting correlation level is included in the medium criteria and describes a positive relationship so that if the Physical Literacy variable increases, the Youth Sport Values variable increases and vice versa. Thus, understanding related to physical literacy and sport values can be used as an important indicator in the physical education learning process that must be considered by teachers